Etika Guru dalam Pelaksanaan Pendidikan Agama Islam di SMA Babul Maghfirah Kuta Baro dan MA Darul Ihsan Darussalam Aceh Besar - Afrianto Afrianto (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Teachers occupy a key position in education and are the ones who influence the ethics of their students. Therefore, a teacher is someone who can be used as a role model, digugu and imitated; both from the personal aspect, knowledge and behavior. The problem is that the reality that occurs in the field, many teachers do not understand this role, so they pay less attention to its implementation in the school environment and in the classroom. The purpose of this research is to find out: (1) Teachers' understanding of SMA Babul Maghfirah Kuta Baro and MA Darul Ihsan Darussalam Aceh Besar about teacher ethics in the learning process of Islamic Religious Education, and (2) Implementation of teacher ethics in the learning process of Islamic Religious Education at SMA Babul Maghfirah Kuta Baro and MA Darul Ihsan Darussalam Kuta Baro Aceh Besar. The research method is descriptive qualitative. The results showed that: (1) PAI teachers have a good understanding of ideal teacher ethics based on Islamic ethical values that refer to the Qur'an and al-Hadith as well as books related to adab / morals; including: the book of ta'lim muta'allim and the book of al Tibyan fi Adabi Hamalah al-Quran, and (2) PAI teachers are able to implement good Islamic ethics in schools with no conflicts that occur, both with fellow teachers and with students. Even PAI teachers are able to be good role models for all school residents, both in attitudes, deeds, speech and actions.